KONSEP EMPOWERMENT SEBAGAI INSTRUMEN PEMBANGUNAN EKONOMI ISLAM DALAM MENGHADAPI PANDEMI COVID-19 DI INDONESIA (TELAAH KRITIS PEMIKIRAN IBNU KHALDUN): KONSEP EMPOWERMENT SEBAGAI INSTRUMEN PEMBANGUNAN EKONOMI ISLAM DALAM MENGHADAPI PANDEMI COVID-19 DI INDONESIA (TELAAH KRITIS PEMIKIRAN IBNU KHALDUN) - Endah Susanti (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2021)
This study aims to see the concepts and theories of development economics based on the Islamic economic point of view of the figure of Ibn Khaldun. The focus in this research is on the concept of Islamic economic development based on Ibnu Khaldun in looking at the concept of community empowerment and its benefits as an alternative to overcoming the problems of economic development after the Covid-19 pandemic that hit Indonesia. This research is a library research with qualitative data and analysis. The results of the study show the economic concept of Islamic development by Ibnu Khaldun, namely First, the Role of Humans “arrijal”. Second, the Role of Development or “al-Imarah” and Justice or “al-adl”. Third, the role of institutions and government. Fourth, the role of wealth or “al-mal”. In his analysis, Ibn Khaldun also emphasized the importance of division of labor and specifications for developing the economy together by promoting the concept of cooperation. From Ibn Khaldun's thoughts on the development of Islamic economics, it is known that the concept of Islamic economic development does not only measure the level of welfare in the world, but more importantly how to achieve prosperity in the hereafter. The concept that is built is more directed at the concept of empowerment or empowerment of natural resources in an efficient and fair manner with the role of upholding ethical values ​​and social justice. The Covid-19 pandemic is a social disaster whose impact is felt by the entire community. The crisis that occurred in 2020 is the biggest public health and humanitarian crisis, which not only causes health emergencies but also provides significant economic losses. Referring to the concept of Islamic economic development by Ibnu Khaldun, efforts to overcome the problem of poverty due to this pandemic are not sufficient only relying on government resources, but also requires the participation and cooperation of all parties. The synergy between the government and the private sector, universities, and other non-governmental institutions needs to be strengthened to accelerate economic recovery in areas affected by the corona virus.